Developing Set of Instructional Instrument of Ecosystem Based on Problem Based Learning (PBL) - Resti, Vica Dian Aprelia; Ibrohim, Ibrohim; Rohman, Fatchur (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Development of learning sets is one of the ways to achieve the goal of education. Learning sets of biology have provide real problem. Student who actively being trained to find real problem solutions are supposed to be able to develop critical thinking skills. Some learning models are able to orient students to meet contextual problem, such as PBL model. The use of PBL model should be integrated in development of learning sets. Development procedures adapted from 4D proposed by Thiagarajan, but this research was only done until the phase of develop. The design step is to determine learning model which relevant to make problem solutions. The result of design step were prototype of the instructional intruments, includes syllabi, lesson plans, student worksheets, media, and assessment which relevant to PBL characteristics and step. In develop step, the prototype of the instrument will be tested by validators (learning sets expert, materials, teacher biology, and media expert) by giving some suggestions and do scoring. Trial test had did at 8th graders in SMPN 4 Malang, a number of 27 students asked to review LKS and media as well as piloting a matter of critical thinking test. Test also did on 7th grade students, consisted of 40 students to do learning activities. The test have not been able to determine the effectiveness of PBM model for improving critical thinking skills, because it was not a quantitative test. Validation result on syllabi, lesson plans, and students worksheets gained very good qualification (above 88%). Critical thinking assessment result showed very good qualification (above 84,5%). Media result showed very good qualification (89,4%). Student worksheet and media according to 8th grade students showed very good qualification (above 84%). The test of critical thinking to 8th grade students showed reliable result and can be used for advance development step. Development test towards 7th grade students haven’t showed integrated of PBM models in learning activities.Keywords:      instructional equipment, PBM model, critical thinking